'I felt like I deserved it because I was autistic': Understanding the impact of interpersonal victimisation in the lives of autistic people. (February 2023) - Pearson, Amy; Rose, Kieran; Rees, Jon
Research suggests that there is a high prevalence of interpersonal violence and victimisation within the autistic population, and that this accounts for poor mental health outcomes. This study aimed to examine the impact of interpersonal violence and victimisation on autistic adults from their own perspective and explore what helps or hinders their recovery. In total, 102 autistic adults completed either an online survey or a spoken interview about their experiences of interpersonal violence and victimisation. We analysed the data using a thematic analysis, and found four themes: (1) The usual for autism (expectations of victimisation, experiences of othering), (2) Personhood revoked: The cost of living (being part of a neurominority, trauma, masking and burnout), (3) Unpacking the baggage (impact of hermeneutical injustice) and (4) ' If you want to make an apple pie from scratch, you have to invent the universe first ' (structural inequality/power dynamics, support and community). Findings highlight the importance of considering the relationship between stigma and victimisation, and the relationship between trauma, masking, and burnout in autistic people. Reducing barriers to support and recovery are contingent on reducing structural inequality and providing better training about autistic people to frontline professionals. Lay abstract: Research suggests that autistic people are more likely to be hurt by someone they know (e.g. a friend or a family member) compared to non-autistic people. In this study, we wanted to know how being hurt by someone you know affects autistic people, and what might help them recover. In total, 102 autistic people took part in an interview, where we asked questions like how being hurt by people they know had made them feel and whether anyone they had asked for help had done a good job of supporting them. We analysed what they had said using thematic analysis, which involved reading what everyone said and looking for common themes. Our findings showed that a lot of autistic people think it is normal to be hurt by people you know because it has happened to them so much. This makes many autistic people feel like they need to mask parts of themselves to stay safe, but this also makes them really exhausted. It took some people a long time to realise what had happened to them was wrong, and it was hard to ask for help. People who did ask for help often had bad experiences with professionals (e.g. police) who did not know much about autistic people. They said better support would come from creating more autistic-run support groups and educating people about autism. These findings are important for working out how to help people who have been hurt by people they know.